Pengaruh Motivasi Hedonis, Browsing dan Gaya Belanja Terhadap Pembelian Impulsif Pada Toko Online Shop (Studi Pada Mahasiswa Universitas Muhammadiyah Yogyakarta) - Sampurno, Toto Pribadi; Winarso, Winarso (Jurnal Manajemen Bisnis, 2015)
This research aims to identify the influence of hedonic motives browsing shopping lifestyle against the impulse buying on online shop. Information which obtained from the results of this study are able to used as a reference for the businesses Online Shop particular fashion item in determining what are the things that affect the imppulsif buying among consumers. Objects of the research conducted at the University of Muhammadiyah Yogyakarta last 6 months of purchase criteria. The technique of data collection used purposive sampling, while the method to collect data used survey method with questionnaires as much as 100 respondent. The data were analyzed by using Statistical Product and Service Solutions (SPSS) version 21.0 with test includes: Validity and Reliability test.This research result showed that hedonic motives positively and significantly effect on the impulse buying, browsing positively and significantly effect on the impulse buying and shopping style positively and significantly effect on impulse buying.Key words: